Nilai-Nilai Pendidikan Tauhid dalam Kitab Aqidatul Awam Karya Sayyid Ahmad Marzuki - Ismail, Ismail; Indra Irawan Sayuti, Sadip; Yuniartin, Ana (Jurnal el-Huda, 2024)
This research aims to (1) find out what values ​​of monotheism education are contained in the book 'Aqidatul 'Awam. The research method used is library research. The primary data source is the book 'Aqidatul 'Lawam, the secondary source is the translation and the tertiary source is the book of sharia (explanation) and also other books that are relevant and relevant to the research. In the book 'Aqidatul 'Awam there are 4 chapters or discussion chapters, namely, chapter I contains the khutbatul kitab, In chapter II there is a discussion of the nature of what is obligatory for Allah, impossible and Jaiz Allah, In chapter III there is a discussion of the nature of what is obligatory for the Messenger, impossible and Jaiz Rasul, In chapter IV there is a discussion of the names of Angels and the names of Prophets. The value of monotheism education that can be taken from the book 'Aqidatul 'Awam by Sayid Ahmad Marzuki explains the value of Divine monotheism education and the value of Insaniyah monotheism education. The values ​​of Divine monotheism education include: Faith, Islam, Sincerity, Piety, Sincerity, Tawakkal, Inabah and Repentance, and Gratitude. Meanwhile, the values ​​of Insaniyah monotheism education include: Love, Brotherhood, Trust, Honesty, Fairness, and Intelligence.